Attack Simulation and Signature Extraction of Low-Rate DoS - Zenghui Liu; Liguo Guan (2010 Third International Symposium on Intelligent Information Technology and Security Informatics, 2010)
LDoS (low-rate denial-of-service) was a new type of DoS attack. In this paper, LDoS attack traffic was simulated on OPNET platform and generated by estimating the retransmission time out (RTO) of normal TCP flow based on the analysis of LDoS attack features, and the performance of targets under the attacking of LDoS was tested. We investigated the cache queue of target router for the purpose of detection and defense of LDoS attack. Test result show that two criterions -- packet percentage and threshold--can detect LDoS attack flows.